Small signal stability assessment and control of power systems. - Mirfendereski, Shojaeddin; Abdul Wahab, Noor Izzri; Jasni, Jasronita; Othman, Mohammad Lutfi (2012)
A method for assessment and control of small signal stability (SSS) has been proposed in this paper. As the angle of rotor represents the stability of the system, the proposed method tries to assess the instability and its solutions by using comparison instead of time consuming conventional method. The idea divides power networks into different areas. The system has sub-controllers and main controller with different authorities which will results in fast and reliable prediction and control of SSS. Artificial intelligence could be used as a tool that would give the ability of learning to the system which gives the system the opportunity to response fast and accurate in future problems.